Uncertainty Determinants of Corporate Liquidity - Christopher F. Baum; Mustafa Caglayan; Andreas Stephan; Oleksandr Talavera (Deutsches Institut für Wirtschaftsforschung (DIW), 2006)
This paper investigates the link between the optimal level of non-financial firms? liquid assets and uncertainty. We develop a partial equilibrium model of precautionary demand for liquid assets showing that firms alter their liquidity ratio in response to changes in either macroeconomic or idiosyncratic uncertainty. We test this hypothesis using a panel of non-financial US firms drawn from the COMPUSTAT quarterly database covering the period 1993?2002. The results indicate that firms increase their liquidity ratios when macroeconomic uncertainty or idiosyncratic uncertainty increases.
Keywords: D92; D8; C23; G32; 330; liquidity; uncertainty; non-financial firms; dynamic panel data; Rentenmarkt; Bid-Ask Spread; Kapitalanlage; Risiko; Börsenumsatz; USA